Women’s Empowerment Status in Menopausal Transition: A Cross-sectional Study - Narjes Bahri; Khadigeh Mirzaii Mirzaiinajmabadi; Habibollah Esmaeily; Robab Latifnejad Roudsari (International Journal of Community Based Nursing and Midwifery, 2022)
Background: Women’s empowerment status in menopausal transition is of great importance due to the increasing trend of life expectancy and population aging. This study was conducted to evaluate the empowerment status of women during the menopausal transition in Gonabad, Iran.Methods: This cross-sectional study was conducted in Gonabad city in Northeast of Iran from April 2017 to March 2018. Cluster sampling was used for selecting 680 women who were in the menopausal transition. Demographic questionnaire and Women’s Empowerment Status Questionnaire - a researcher-made questionnaire- was used for data collection. Pearson’s correlation coefficient, one-way ANOVA, and linear regression were used to analyze the data using SPSS version 16; A p-value less than 0.05 was considered as significant.Results: The majority of the participants (510; 76.10%) had a high empowerment level. A high empowerment status in the family, economic, social, and health domains was observed in 499 (74.50%), 534 (79.70%), 523 (78.05%), and 493 (73.60%) participants, respectively. The majority of the participants had moderate empowerment status in political (427; 70.40%) and religious domains (464; 69.30%). There was a negative correlation between the total empowerment score and the participants’ age (P<0.001), husband’s age (P<0.001), and the number of children (P<0.001). There was a positive correlation between the total empowerment score and education (P=0.003) as well as age of marriage (P=0.03).Conclusion: Overall empowerment status of women in menopausal transition in Gonabad -Iran was high. However, in political and religious domains, the status was moderate. We suggest that empowered women should be invited to share their experiences with other females. Development of social networks could provide the basis for sharing the experiences of these women and helps policy makers to develop community empowerment programs.